Design of Rectangular Patch Microstrip Antenna with Rectangular Slot on 2.4 GHz Ground plane for Wifi Application - Gebriola Permata Isra; Nasrul Nasrul; Yulindon Yulindon (Politeknik Negeri Padang, 2024)
This research aims to design a rectangular patch microstrip antenna design with rectangular slots on the 2.4 GHz ground plane for Wi-Fi applications using CST Studio Suite 2019 software and antenna measurements using Vector Network Analyser. Some of the antenna parameters produced are return loss, bandwidth, VSWR, radiation pattern, and gain. This antenna has a rectangular patch shape and has a ground plane that has a rectangular slot. The antenna is designed on a circuit board (PCB) with a permittivity of 4.6 and a thickness of 1.6 mm. The antenna is designed based on the characteristics of several antenna parameters, namely having a return loss-10 dB gain value ≥1 dB, and VSWR < 2 dB. After several simulations, the results at a frequency of 2.4 GHz obtained a return loss value of -14.84 dB, a bandwidth of 53 MHz, a VSWR value of 1.442, a gain of 2.063 dbi, and has a Unidirectional radiation pattern. The measurement of the fabricated microstrip antenna using a Vector Network Analyser shows a return loss value of -11.68 dB, and a VSWR of 1.747 dB.